Heat transfer to two phase flow and fouling mitigation by synthetic fibre additives / Thineskumar Ramalingam - Thineskumar, Ramalingam (2022)
One of the most notable logical premiums is the investigation of the conduct of fibre suspension streams, since adding a little amount of fibre to the water modifies the stream's behavior. Textile industries are one of the most important businesses that use fibre suspensions, which has led to a rise in the use of synthetic fibres as an alternative source. As a result, investigating the heat transfer and fouling resistance patterns of synthetic fibre suspension in annular flow appears to be critical. A total of six concentrations with six different velocities ranging from 0.0025 wt. percent up to 0.1 wt. percent and from 0.1 m/s to 0.35 m/s were used in this study for a specific synthetic fibre, the Nylon 6,6 fibre, in which a total of six concentrations with six different velocities ranging from 0.0025 wt. percent up to 0.1 wt. percent and from 0.1 m/s to 0. The varied concentrations and velocities were then evaluated under three distinct constant heat flux boundary conditions, with specimen surface temperatures of 50°C, 60°C, and 70°C, respectively. Heat transfer was found to be enhanced. For carbonate fouling in de-ionized water (DI Water), an experimental study was conducted using a combination of sodium bicarbonate and calcium chloride. Using a constructed monitoring system, the impacts of various factors on the calcium carbonate scale development process were explored experimentally. The rates of calcium carbonate deposition in suspension with and without Nylon 6,6 additions (only DI Water) were compared. Analytical microscopy was used to evaluate the shape of the deposit layer on the surface.